Benign cellular fibrous histiocytoma in a rare location—A toe - Shivani Parihar; Kevin Ho; Paul S. Armanasco (Foot & Ankle Surgery: Techniques, Reports & Cases, 2022)
A cellular fibrous histiocytoma (CFH) is a variant of fibrous histiocytomas with increased cellularity with a fascicular growth pattern and increased frequency to extend into the subcutis. CFH is a benign nodular growth with a high recurrence rate of 26%. It is regularly confused with dermatofibrosarcoma protuberans and leiomyosarcoma due to their morphological similarities, hence emphasizing the importance of proper diagnosis. In this article, we discuss the case of a 50-year-old male who presents with a recurrence of CFH 30 years post-excision. The 15mm lesion on the right fourth toe was previously excised and misdiagnosed as a granuloma. In regard to the current case, a surgical excision was performed without complications, and histopathology testing confirmed the diagnosis of CFH . To date, there is no occurrence of a CFH on the toe reported in literature.